Optimizing Early Detection of the Intelligence Unit to prevent the spread of radicalism in the Jepara Police Legal Area - Rachman, Arshan (Advances in Police Science Research Journal, 2024)
Radicalism has become one of the problems faced by Indonesia at the global, regional, and national levels. This is because radicalism is the foundation of the thought, ideology, and ideas behind terrorist acts that disrupt the security and order of society. The function of Intelligence Unit under the Indonesian National Police, as law enforcement officials responsible for domestic security, plays a role in the surveillance of radicalism. The Intelligence Unit of the Jepara Police Resort as the intelligence agency of the Indonesian National Police in Jepara Regency plays a leading role in early detection and warning in facing radicalism. Therefore, the purpose of this thesis is to provide input and suggestions for optimizing the early detection of the Intelligence Unit in order to prevent the spread of radicalism within the jurisdiction of the Jepara Police Resort. In this thesis, the SWOT Theory, Management Theory, Competency Theory, and Cooperation Theory are used as analytical tools to break down issues into researchable problems using a qualitative case study approach. Data triangulation and interactive data analysis models are used as a means of examining the validity and analysis of the data obtained. Using the concepts of Predictive Policing, Organizational Development, and Social Capital, problem-solving is carried out with the result of the need for optimization at each management stage, the need to improve the 3 elements of personel competence, and the need for cooperation with all relevant components.